Structure and chemical-physical characteristics of lactate dehydrogenase-elevating virus and its RNA. - Brinton-Darnell, M (1975)
Lactate dehydrogenase-elevating virus (LDV) was purified from culture fluid of infected primary cultures of various mouse tissues (peritoneal macrophage, bone marrow, spleen, and embryo) and from plasma of infected mice. Electron microscopy of negatively stained virus and positively stained sections of LDV revealed spherical particles of uniform size with a diameter of about 55 nm, containing an electron-dense core with a diameter of about 30 nm. During sample preparation the envelope had a tendency to slough off and disintegrate to form aggregates of various sizes and small hollow particles with a diameter of 8 to 14 nm. Two strains of LDV exhibited a density of 1.13 g/cm3 in isopycnic sucrose density gradient centrifugation whether propagated in primary cultures of the various mouse tissues or isolated from plasma of infected mice. A brief incubation of LDV in a solution containing 0.01% Nonidet P-40 or Triton X was sufficient to release the viral nucleocapsid, whereas a similar treatment had no effect on Sindbis virus. The nucleocapdis of LDV exhibited a density of 1.17 g/cm3, was devoid of phosphatidylcholine, and contained only the smallest of the viral proteins, VP-1, which had a molecular weight of about 15,000. The envelope contained two proteins. VP-2 with a molecular weight of 18,000 and a glycoprotein, VP-3, which migrated heterogenously (24,000 to 44,000 daltons) during polyacrylamide gel electrophoresis. When compared to the sedimentation rate of 29S rRNA, the RNAs of LDV and Sindbis virus sedimented at 48 and 45S, respectively, whether analyzed by zone sedimentation in sucrose density gradients containing low or high salt concentrations or denatured by treatment with formaldehyde. Our results indicate that LDV should be classified as a togavirus, but that LDV is sufficiently different from alpha and flaviviruses to be excluded from these groups.